Export Uncertainty and Geopolitics: Why is Regional Integration Not Yet Successful in Central Asia? - Soham Das (Ukrainian Policymaker)
Central Asia is a fascinating region which has seen a lot of transformations in the past two hundred years. After their inauguration as independent republics in 1991, they faced the prospect of an economic transition. There were many challenges. Central Asian republics suffer from some of the fundamental infrastructural problems of landlocked countries. They are also far from the global markets. Regional integration in Central Asia has so far been mostly about formal international organizations. A specific model for multilateral institutional cooperation has not developed yet, and there is a low level of regional economic inter-dependence. This paper aims to explore why regional integration efforts has not yet been successful in the region of Central Asia. The paper would analyse this chronologically, mainly from the perspectives of export uncertainty and geopolitics.